Faith Growing in Action: Implications of John Locke's Tabula Rasa Concept and Ecological Education for HKBP Sunday School Children - Frans Jaswin Manalu, Musdodi (Religi: Jurnal Studi Agama-agama, 2024)
This article explores the integration between John Locke's concept of tabula rasa and ecological education for Sunday School children in the Huria Kristen Batak Protestan (HKBP) Church. Titled "Growing Faith in Action," this research investigates how Locke's philosophical concept of the mind as an empty "tabula rasa" filled with experience and learning can be applied in the context of children's growing faith. This research focuses on ecological education as a means for Sunday school children's faith growth that involves their understanding of their relationship with nature and the surrounding community. The concept is applied specifically in the context of HKBP Sunday School, highlighting the church's efforts to deliver religious teachings and facilitate hands-on experiences that can shape children's faith. Combining Locke and Susan Power Bratton's thoughts on ecological education and the ecclesial context, this article offers insights into how faith can develop through concrete action and experience, creating a solid foundation for children's spiritual growth in an ecologically conscious and active learning ecclesial environment.